Pelayanan Jaringan Internet Bagi Pelanggan Indihome di Kabupaten Merauke - Andri Irawan; Yudi Tristanto (Jurnal Administrasi Karya Dharma, 2022)
In the industrial revolution 4.0, people have been required to always be literate in information technology, one of which is internet technology which is a data network that connects the whole world. This study aims to describe the efforts made by PT. Telkom Merauke in improving the quality of its services to the community, as well as what factors influence it. This study used a qualitative descriptive approach where the research data were obtained from observations and interviews. The results of the study indicate that the Telkom Merauke Office in providing new installation services for Indihome is currently quite good. this can be seen from the completion time of the new Indihome installation which takes 3 (three) days with an installation fee of Rp. 550,000. Including the state of public services related to this pandemic period, one of the breakthroughs that has been launched is the MyIndihome application. The goal is that Indihome customers from home can download the application then choose the new Indihome installation feature, then come to the Telkom office to apply for a new Indihome installation. Factors influencing the process of installing new Indihome services at the Telkom Merauke Office. These factors consist of supporting factors such as office infrastructure and innovations. Meanwhile, the inhibiting factors are public awareness, lack of public awareness in preparing the requirements for the new installation of Indihome so that services cannot be carried out optimally.